Energy demand analysis of a five star hotel in Nepal- A case study of Bhairahawa, Nepal. - Acharya, Shadananda; Shakya, Shree Raj (Journal of Innovations in Engineering Education, 2021)
The tourism sector is one of the most vital sectors for economic development. Hotels consumed a bulk amount of energy to satisfy the guest needs. This study to development of energy mix concept in the hotels sector to minimize the crisis of energy in the future determine electrical and thermal energy consumption patterns of a hotel. The low Emission Analysis Platform (LEAP) model was used to analyze energy demand and greenhouse gas emission under different scenarios. The base year for the study was 2019 and the end year up to 2040. It has been estimated that the base year electrical and thermal consumptions were 16.3 Tera joule and 9 tera joule respectively. Energy consumption is expected to be increased from 25.3 tera joule to 65.9 tera joule in 2040 under the business as usual scenario (BAU). In efficient lighting scenario, energy consumption will be 2 tera joule in 2040. In efficient heating ventilation and air conditioning scenario, efficient cooking scenario and steam generation scenario, energy consumption will be 12 tera joule, 6.5 tera joule and 4.2 tera joule in 2040. In the combined policy scenario, energy consumption will be 37.76 tera joule in 2040. Which result saving of 28.14 tera joule as compared to BAU scenario. This study also show the greenhouse gas emission will be 1100 metric tons of carbon dioxide equivalent in 2040 under business as usual scenario. After the implementation of the efficient system, greenhouse gas emissions will gradually reduce and reach zero in 2035 to 2040. Similarly, per capita greenhouse gases emissions will gradually reduce and reach zero in 2035 to 2040. Thus a large amount of energy can be saved and the large quantity of greenhouse gas emissions can be stopped by applying the combined policy scenario.